Guidelines for managing abnormal situations (John Wiley & Sons, Inc., 2023)
"Abnormal situations within the process industry occur when there is a disturbance in a process where basic process control system cannot cope. In the context of hazard evaluation procedures this can be viewed as a deviation. Abnormal situations that developed or occurred have resulted in adverse events that could have been prevented. Process plants often rely on complex control systems along with various tools and techniques including intelligent system to help manage such issue. However, such automated solutions are not always effective and can worsen the occurrence, particularly when it leads to confusion on the part of the operators. Some of the events are associated with non-typical conditions can be identified and managed through careful consideration as to how they may occur and by developing methods to prevent or mitigate the consequences of an event"-- Provided by publisher.
Keywords: Chemical plants -- Safety measures.; Chemical processes -- Risk assessment.; Chemical plants -- Management.; elektronické knihy; electronic books